The Effect of Some Forage Additives Used in Feeding of Growing Finishing Pigs - Tiberiu Polen (Scientific Papers Animal Science and Biotechnologies, 2023)
The experiment was carried out over a group of 50 growing finishing pigs, allotted into two equal groups. The control group (C) received a basal diet supplemented with a 2% premix – vitamins and microelements as oxides and salts mixed with maize flour-based diet; the experimental group (E) received the same diet supplemented with 2% premix made of vitamins and microelements as chelated phosphoric glass on zeolite based diet. At the end of our research it was revealed that group (E) obtained a better growing gain (12.1%), a 5.4% greater feed intake and a feed conversion rate reduction of 6.5% versus group (C).